DSP-based torque control strategy for direct-driven five-phase PM BLDC motor for electric vehicles - Teng, Lin Fong. (2010)
Permanent-Magnet Brushless Direct-Current (PM BLDC)motor drives have the excellent capability of producing high torque, which make them suitable for direct-drive applications. With its advantages of small size, low inertia, quick response and accurate speed control, PM BLDC motor drive is very suitable for applications in electrical vehicles. However, torque pulsation surfaces when conventional current controller is used. In this report, a strategy for torque control of five-phase PM BLDC direct-driven wheel motor drive based on the Variable Structure Strategy (VSS)is documented.